2013
DOI: 10.1002/ajpa.22449
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of health in prehistoric mainland Southeast Asia: Indicators of stress in response to the intensification of rice agriculture

Abstract: Numerous bioarcheological investigations have suggested that as agriculture intensifies, levels of physiological stress and poor health increase. However, previous research in Southeast Asia suggests that a decline in health was not universal. This study aimed to provide the first investigation of human health during the intensification of rice agriculture in the large skeletal sample from the prehistoric site of Ban Non Wat, Northeast Thailand (1750-420 b.c.). Health was analysed using two indicators of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Again, Wood et al (1992, p. 355) express this as a hypothesis that is just as consistent with the data at hand as several other hypotheses, not as an idea that they ''believe'' to be true. Scholars have repeatedly attributed this new binary view-that skeletal lesions indicate relatively good health and an absence thereof indicates poor health-to Wood et al over the last 20 years (e.g., Clark et al 2014;Welinder 2001;Wright and Chew 1998), despite their attempt at clarification in their reply to the comments. Wood et al encourage thinking that goes beyond simple binary distinctions.…”
Section: Immediate Reactions To the Osteological Paradoxmentioning
confidence: 99%
“…Again, Wood et al (1992, p. 355) express this as a hypothesis that is just as consistent with the data at hand as several other hypotheses, not as an idea that they ''believe'' to be true. Scholars have repeatedly attributed this new binary view-that skeletal lesions indicate relatively good health and an absence thereof indicates poor health-to Wood et al over the last 20 years (e.g., Clark et al 2014;Welinder 2001;Wright and Chew 1998), despite their attempt at clarification in their reply to the comments. Wood et al encourage thinking that goes beyond simple binary distinctions.…”
Section: Immediate Reactions To the Osteological Paradoxmentioning
confidence: 99%
“…Therefore, this factor could not impact ameloblasts. Simultaneous evaluation of body height and MIH was a new topic that was measured in this study by Clarck et al [ 31 ] Data showed although average of body height in MIH group was lesser than control group, it was not statistically meaningful. Multifactorial process terminate to MIH and body height and some of them were inevitable in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, most early Southeast Asia groups were relatively healthy (Domett and Tayles 2007;Douglas and Pietrusewsky 2007;Ikehara-Quebral 2010;Oxenham et al 2006;Pietrusewsky and Douglas 2002) compared to groups that adopted intensive agricultural practices elsewhere (Cohen and Armelagos 1984;Cohen and Crane-Kramer 2007). Furthermore, there is no evidence in several Southeast Asia groups that an increased reliance on rice contributes to poorer health (Clark et al 2014;Tayles et al 2000) and no clear temporal trend of declining oral-dental health, which varies with the health indicator assessed (Ikehara-Quebral 2010; Newton and . However, Newton (2014) suggested that late Iron Age samples from Phum Snay and Phum Sophy show a high dependence on agricultural foods and she demonstrated a decline in health likely coinciding with an intensification of agriculture.…”
Section: Discussionmentioning
confidence: 99%